Fractionational and structural characterization of lignin and its modification as biosorbents for efficient removal of chromium from wastewater: a review - Bing Wang (Journal of Leather Science and Engineering, 2019)
Abstract The removal of chromium (Cr) from wastewater by various adsorbents has been investigated. As compared with the commercial activated carbon, the biosorbents with inexpensive and high adsorption capacities are developed from lignocellulosic wastes. Lignin, existing in lignocellulosic biomass, is the second most abundant resource in nature. Recently, lignin-based bio-sorbents were served as an advanced novel material for the metal ions and dye adsorption from wastewater. It has showed several advantages in the wastewater treatments because of the low-cost, high adsorption capacity, easy recover, and possibility of metal recovery. In this review, the isolation of lignin from lignocellulosic biomass was summarized, and the structural characteristics of lignin were comparably analyzed. The modification of lignin was performed to obtain a large surface area, strong binding-site, and high and quick adsorption properties of lignin-based adsorption materials. The adsorption efficiency of Cr ions was found to be strongly dependent on the pH of the wastewater. To further illustrate the adsorption process, the structural changes and the interactions between the metal ions and the functional groups of the lignin-based biosorbents in the adsorption process should be further investigated. Once the cost-effective and high-efficiency modification techniques are developed, lignin-based adsorbents can be expected to be the most suitable alternatives for Cr ions removal from wastewater in industry. Graphical abstract Fractionational and structural characterization of lignin and its modification as biosorbents for efficient removal of chromium from wastewater.